UJI AKTIVITAS ANTIJAMUR EKSTRAK ETANOL KULIT BATANG RAMBUTAN (Nephelium lappaceum L.) TERHADAP JAMUR Candida Albicans SECARA IN VITRO - Pangalinan, Frendsiane; Kojong, Novel; Yamlean, Paulina (UNIVERSITAS SAM RATULANGI, 2012)
Fungal infections are often found in people in tropical countries including Indonesia because theclimate is hot and humid making it easier for mold growth. Empirically Rambutan bark(Nepheliumlappaceum L.) used to treat ulcers caused by the fungus Candida albicans. Theexperimentwasaimed to know the antifungal activity of ethanol extract of Rambutan bark againstCandida albicans and the effect of increasing concentrations of the Rambutan bark ethanol extract tothe antifungal activity. Rambutan bark ethanol extract obtained from the maceration process insamples of wet and dry samples are prepared with concentrations of 10%, 20%, 40% and 80%.Antifungal activity test was done by difussion method of well treatment to know the antifungaleffectiveness by observing the inhibition zone. The resultof the experiment that effective Rambutanbark is used to inhibit the antifungal activity against Candida albicans. One way ANOVA test showedthat there were significant differences in inhibition zone diameters and followed by Duncan test with aconfidence level of 5% showed the highest inhibition zone diameters at a concentration of 80% andketoconazole(+)control.Key words: Antifungals, Nepheliumlappaceum L., difussion method, Candida albicans